Hot water epilepsy under 3 years of age: A short term follow-up study (Annals of Medical Research, 2021)
Aim: Hot water epilepsy (HWE) is a type of reflex epilepsy that occurs as a result of immersing or pouring hot water over the head. Clinical and laboratory findings and short-term neurodevelopmental outcomes of patients were discussed in this report.Materials and Methods: Eight patients under the age of three and followed-up with a diagnosis of HWE between 2017 and 2020 were enrolled in the study. Patient files were evaluated retrospectively.Results: All our patients except one were boys. The patients’ mean age at admission was 16.6 months (min: 10, max: 36), and the mean follow-up period was 13.5 months (min: 6, max: 25). Two patients also experienced non-reflex motor seizures not related to bathing, and these received daily oral antiepileptic therapy. Six patients had focal onset secondary generalized seizures, while one had focal seizures and one has hypomotor seizures accompanied by loss of consciousness. neurodevelopmental milestones were compatible with the patient’s age in all followed-up cases. Clobazam administration before bathing is currently an effective and easily applicable method for this condition.Conclusion: Hot water epilepsy is mostly benign. Clobazam before bathing is an effective option. Daily oral antiepileptic therapy should be administered to patients with seizures accompanying HWE.
Keywords: Childhood; clobazam; hot water epilepsy